A study on shear strength of fibre reinforced soil / Chrisnadia Sinam - Sinam, Chrisnadia (Faculty of Civil Engineering, 2005)
There are several methods for improving the strengths of soils. Reinforced Earth Technique is one of them. It was systematically introduced by a French scientist H. Vidal in 1966. Reinforced Earth is a composite material which is formed by the association of soil and tension resistant reinforcing elements in the form of sheet, strips, nets or mats of metal, synthetic fabrics of fibre-reinforced plastics and arranged in the soil mass in such a way that reinforcement reduces or suppresses the tensile strain which might develop under gravity or boundary forces. The other way of improving the strength is by mixing fibres in the soil, the composite material so formed is termed as Fibre Reinforced Soil. The reinforcement suppresses the normal tensile strains in the soil mass through frictional interaction. Insertion of reinforcing elements in the soil mass modifies the strength of soil, which in shear strength tests appear either as an increased friction angle or as a cohesion intercept of Mohr envelope. The load deformation response of a reinforced soil can therefore be expected to be an improvement over the unreinforced soil. Keeping in view the above facts, a basic study was carried out in laboratory to study the effect of fibres on the shear strength of soil by conducting direct shear tests. The effect of angle of inclination of fibres, number of fibres, and length to diameter ratio of fibres was studied. Pull-out tests were also conducted to find out the coefficient of friction between fibre and soil. Effect of over burden pressure on coefficient of friction between soil and reinforcement was also studied. Shear strength of soil was found to increase with the inclusion of fibres.